2019
DOI: 10.1039/c9cc05051e
|View full text |Cite
|
Sign up to set email alerts
|

Location matters: cooperativity of catalytic partners in porous organic polymers for enhanced CO2 transformation

Abstract: Functionalities with corrected inter-site distance in porous materials enable them to work in a concerted manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 57 publications
0
16
0
2
Order By: Relevance
“…As shown in Fig. S7B, † the catalyst VIPA-Br could afford high yields of 96% and 98% at higher temperatures (40 C and 50 C) in a short time of 24 h. To the best of our knowledge, the remarkable catalytic activity in the conversion of ECH with atmospheric CO 2 (yield of 99%, 30 C for 72 h; yield of 96%, 40 C for 24 h) over the metal-free heterogeneous catalyst VIPA-Br could surpass the catalytic behaviors of many reported halogen-based iPOPs, and even was comparable to those of iPOPs with electrophilic HBDs or metal sites (see Table S3 † for details), [13][14][15][16][17]22,23,25,46,[58][59][60][61][62][63][64] and some other types of catalysts (e.g., bio-based catalysts) with the help of co-catalysts such as tetrabutylammonium iodide (TBAI), 36,65,66 and was only inferior to the catalytic activities over a few iPOPs with metal sites. 67,68 In addition, from the perspective of green and sustainable chemistry, the design and use of metal-/halogen-free catalysts are new orientations, [69][70][71][72] but they still need to improve the catalytic performance at CO 2 atmospheric pressure and low temperatures compared with halogen-based catalysts such as the present catalyst VIPA-Br.…”
Section: Catalytic Performance In Co 2 Conversionmentioning
confidence: 99%
“…As shown in Fig. S7B, † the catalyst VIPA-Br could afford high yields of 96% and 98% at higher temperatures (40 C and 50 C) in a short time of 24 h. To the best of our knowledge, the remarkable catalytic activity in the conversion of ECH with atmospheric CO 2 (yield of 99%, 30 C for 72 h; yield of 96%, 40 C for 24 h) over the metal-free heterogeneous catalyst VIPA-Br could surpass the catalytic behaviors of many reported halogen-based iPOPs, and even was comparable to those of iPOPs with electrophilic HBDs or metal sites (see Table S3 † for details), [13][14][15][16][17]22,23,25,46,[58][59][60][61][62][63][64] and some other types of catalysts (e.g., bio-based catalysts) with the help of co-catalysts such as tetrabutylammonium iodide (TBAI), 36,65,66 and was only inferior to the catalytic activities over a few iPOPs with metal sites. 67,68 In addition, from the perspective of green and sustainable chemistry, the design and use of metal-/halogen-free catalysts are new orientations, [69][70][71][72] but they still need to improve the catalytic performance at CO 2 atmospheric pressure and low temperatures compared with halogen-based catalysts such as the present catalyst VIPA-Br.…”
Section: Catalytic Performance In Co 2 Conversionmentioning
confidence: 99%
“…Solid-state 31 P NMR spectra of PQPBr and PQPBr-2OH in Figure 4b showed a main peak with a small peak at around 19.8 ppm and −7.7 ppm, respectively. The peak at 19.8 ppm can be attributed to the phosphorus atoms of the phosphonium salts [45,51], while the small peak at around −7.7 ppm should be assigned to a small amount of unfunctionalized phosphine [44,51]. These findings further indicated that most of P atoms in PQPBr and PQPBr-2OH was successfully alkylated by alkyl bromide.…”
Section: Characterizations Of the Polymeric Catalystsmentioning
confidence: 79%
“…These decreases of physical properties could be assigned to the partial pore filling after functionalization with alkylation groups. In spite of the obvious decrease in BET surface areas with this post-modification method, the obtained PQPBr, PQPBr-OH, and PQPBr-2OH still possessed higher surface areas than that of polymeric quaternary phosphonium salts preparing by direct polymerization of vinyl-functionalized quaternary phosphonium salts in N,N-dimethylformamide (DMF) solvent [43,44]. These high BET surface areas might be attributed to the use of THF as a solvent for the polymerization and alkylation reactions; THF showed excellent swelling properties towards the phosphine-functionalized porous polymer that was prepared by the polymerization of vinyl-functionalized monomers [47,48].…”
Section: Characterizations Of the Polymeric Catalystsmentioning
confidence: 97%
“…(POPs)和结晶共价有机框架材料(COFs) [4] . [5] , 并研究它们在 CO 2 环加成反应中的催化性能 [6] . 结果表明: 羟基的引入以 及羟基与季鏻盐相对位置对催化效率有重要影响.…”
unclassified
“…当羟基处在季鏻盐的间位时大幅降低了反应的活化 能, 相比于不含羟基的材料, 其活化能降低了约 1.4 倍 (96.75 kJ•mol -1 vs. 134.64 kJ•mol -1 ), 为此, 催化性能随 之提升了 2.5 倍. 图 2 聚季鏻盐结构式 [5] Figure 2 Structures of polymeric phosphonium salts [5] 除了引入辅助基团的策略之外, 溶剂筛选是我们最 常用的调控反应次级环境的手段. 许多反应在 N-甲基 吡咯烷酮(NMP)等高沸点的非质子化溶剂中表现出优 异的性能, 但是, 由于其难挥发的不足, 这些溶剂的使 用对产物分离带来极大的困难, 不仅耗时、耗能甚至还 会在分离过程中导致副反应的发生.…”
unclassified